Children with Attention-Deficit/Hyperactivity Disorder: Normalising childhood in contemporary biopolitical societies - Lekka, Vasia (The Greek Review of Social Research, 2024)
This article examines the persistent and continuously increasing diagnosis of ADHD in children within Western societies and the attempt to normalise childhood. Having as a point of departure the Foucauldian theory and the tools of the new sociology of childhood, our target is to delineate the consequences of this diagnosis regarding the notion of the “child” per se and what is constituted as “normal” and “pathological” childhood and, consequently, regarding the construction of children’s new identities and new subjectivities within biopolitical societies at the beginning of the 21st century.